Fibrinogen A Alpha-Chain Amyloidosis in Two Chinese Patients - Li, Zhen-Yu; Wang, Shuang; Li, Dan-Yang; Liu, Dan; Wang, Su-Xia; Yu, Xiao-Juan; Liu, Gang; Zhou, Fu-De; Zhao, Ming-Hui (Frontiers in Medicine, 2022)
Objectives: Fibrinogen A alpha-chain amyloidosis (AFib amyloidosis) is the most common form of hereditary renal amyloidosis in the United Kingdom and Europe, but has rarely been reported in Asia. In this study, we reported two AFib amyloidosis patients with novel mutations in China, reviewing the literature and summarizing main characteristics of AFib amyloidosis in Asia. Methods: Two unrelated Chinese patients were diagnosed with AFib amyloidosis by clinical presentation, renal biopsy, mass spectrometry and DNA sequencing in Peking University First Hospital of China from 2014 to 2016. Results: Both of the patients presented with proteinuria, edema and hypertension. Renal biopsies of two patients showed extensive amyloid deposits (Congo red positive) in glomeruli, and focal tubulointerstitial amyloid deposits was also found in patient 1. Besides, hepatic involvement of amyloidosis has been detected by liver biopsy in patient 1. By electron microscopy, randomly arranged fibrils in a diameter of 8-12nm was identified in mesangial matrix and subendothelial area of glomeruli. Immunohistochemistry demonstrated amyloid deposits were strongly positive for fibrinogen Aα in glomeruli and positive for LECT2 in the interstitium of renal medulla and the liver in Patient 1. Unevenly positive staining for both fibrinogen Aα and ApoA-I were found in Patient 2. Fibrinogen Aα was the most abundant amyloidogenic protein in both patients identified by laser microdissection and mass spectrometry-based proteomic analysis. Genetic analysis revealed the fibrinogen A a-chain gene (FGA) mutation in both patients, including a new insertion mutation (c.1673_1674insA) in Patient 1 and a new deletion mutation (c.1639delA) in Patient 2. Genetic analysis of the LECT2 gene in patient 1 revealed a codon change from ATC to GTC at position 172, which is a common polymorphism in all ALECT2 amyloidosis patients. Conclusions: We reported two AFib amyloidosis patients in China, both of them had new mutations of the FGA, one of them coexisted with ALECT2 amyloidosis simultaneously.